A modified predilation, sizing, and postdilation scoring system for patients undergoing metallic drug‐eluting stent implantations. (7th January 2020) - Zhao, Xueyan; Guan, Changdong; Yuan, Jinqing; Xie, Lihua; Wang, Huan; Hou, Shuang; Zhang, Min; Zhang, Xinbo; Gao, Runlin; Xu, Bo
Abstract: Objective: This study sought to assess whether the predilation, scaffold/stent sizing, and postdilation (PSP) score for bioresorbable scaffold (BRS) implantation was associated with outcomes following metallic drug‐eluting stent (DES) implantation. Background: The PSP score is associated with patients' prognoses after BRS implantation. Methods: This study involved 2, 348 patients who underwent biodegradable polymer DES implantations during the PANDA III trial. The optimal PSP technique was defined according to previous studies of BRS implantations. The main outcome was target lesion failure (TLF) that comprised cardiac death, target‐vessel myocardial infarction, or ischemia‐driven target lesion revascularization. Results: Twenty‐five (1.1%) patients fulfilled all the PSP criteria. The BRS‐derived PSP score was of limited prognostic value for 2‐year TLF after metallic DES implantation; optimal sizing was a protective factor, but optimal predilation was a risk factor. We built a new PSP model for DESs by identifying the following risk factors: predilation performed with a residual stenosis ≥70% or a balloon‐to‐quantitative coronary angiography (QCA)‐determined reference vessel diameter (RVD) ratio >1:1, sizing performed with an RVD <2.25 mm or a stent diameter >0.25 mm wider than the QCA‐RVD, a postprocedural stenosis diameter ≥30%, age, and the baseline SYNergy between percutaneous coronary intervention with TAXus and cardiac surgery (SYNTAX) score. The new PSP scoring system predicted 2‐year TLF (area under the curve, 0.69; 95% confidence interval, 0.65–0.73); a cutoff value of 19.2 points identified high‐risk patients. Conclusions: The new PSP scoring system, based on redefined PSP criteria, age, and the SYNTAX score, could help optimize metallic DES implantations.